Analysis of The Implementation of Independent Curriculum Assessment Assessment in English Courses at Elementary School - Surul, Rofiatus (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2022)
Education is an effort made by humans to hone and maximize the potential that is in them. So to support the achievement of the educational goals listed in the law it is necessary to have good collaboration from various elements of education including educators and students as actors in realizing educational goals. the existence of an independent curriculum is also an effort by the government to overcome the setback in education which is the impact of the existence of covid. In the Independent Curriculum, principals and educators are given the freedom to develop lesson plans, implement learning and develop curricula based on the needs of students. assessment is the initial step for evaluating and planning further learning, in general the purpose of the assessment is to see the learning outcomes of students. Assessment in the independent curriculum is completely left to educators in which the form of assessment is divided into two, namely formative and summative assessment. English is a tool for communicating orally and in writing. The approach used in this study is a qualitative approach. While the type of research used in this research is descriptive by using purposive sampling technique. The data collection method includes three stages, namely observation, interviews and documentation. Data analysis techniques namely data reduction, data presentation, drawing conclusions. Meanwhile, to test the validity of using source triangulation and technique triangulation. With the results of the research that the implementation of the independent curriculum at SDN 07 Kaliwining rambipuji received a good response with the implementation of various assessments listed in the independent curriculum such as written tests, oral tests, portfolios and projects in learning English, and supported by the existence of worksheets for support student knowledge and facilitate educator assessment.